Eating as spiritual practice for the peaceable kingdom - Rosell, Ruth Lofgren (Review and expositor, 2022)
The prophetic image of a peaceable kingdom is a hopeful vision of justice for the oppressed, peace between nations, harmony between humanity and other living creatures, and the flourishing of creation. Today, the climate crisis poses new threats to these hopes. Because raising animals for food contributes to the climate crisis, I propose plant-based eating as a spiritual practice for the peaceable kingdom. This practice involves eating in ways that produce the least amount of greenhouse gases, as well as reduce greatly the suffering and killing of animals. Climate scientists report that eating such a plant-rich diet is one of the most effective ways individuals and communities can address the climate crisis. Support for such a practice is found in the Genesis origin narratives and the Christian priority of love.